GOVERNMENT REGULATION IN LIEU OF LAW NUMBER 2 OF 2022 CONCERNING EMPLOYMENT CREATION IN PERSPECTIVE - Susilowardani Susilowardani (Bajang Institute, 2023)
The purpose of this study is to review the urgency of issuing Perppu Number 2 of 2022 and what is the business law perspective in responding to the ratification of Perppu Number 2 of 2022. The research method used by the author is normative legal research conducted by analyzing the substance of the Perppu Cipta Kerja. The author considers that the Job Creation Perppu has no urgency to force the Government to issue it, because it is precisely an assessment of stable economic conditions and nothing threatening. Even if the threat of a global recession is something to be feared, then Indonesia can adopt the principle of reciprocity in facilitating trade between countries. Perppu Cipta Kerja when viewed from a business law perspective, it will concern two things, namely regulations governing entrepreneurs or business people and regulations governing workers. Workers feel disadvantaged by the existence of the Perppu Cipta Kerja because of the rules that are not in their favor, such as the abolition of long leave, uncertainty in wages, and criteria for outsourced workers (outsorcing). On the other hand, entrepreneurs actually benefit from the Perppu Cipta Kerja's commitment to the policy of empowering MSMEs and improving the investment ecosystem, which is expected to increase investment so that many workers can surrender